Addison's Disease Presenting as Acute Renal Failure and Hyperkalemic Paralysis: A Rare Presentation. (22nd December 2021) - Jana, Kundan; Janga, Kalyana; Greenberg, Sheldon; Gulati, Amit
Abstract : Hyperkalemic paralysis in the setting of acute renal failure can lead to a missed or delayed diagnosis of adrenal insufficiency as the raised potassium can be attributed to the renal failure. Acute kidney injury as the presenting manifestation in an adrenal crisis due to Addison's disease has been rarely reported in the literature. Here, we present the case of a young 37-year-old male who came with hyperkalemic paralysis and acute renal failure needing emergent hemodialysis. He had no past medical history and no medication history. His hyponatremia, hypotension, and hyperkalemia pointed to a picture of adrenal insufficiency confirmed by undetectable serum cortisol, elevated ACTH, renin, and low aldosterone levels and imaging. Replacement steroid therapy was given, and the patient made a steady recovery. He was advised on the importance of compliance to treatment at discharge to prevent another crisis event. Acute renal failure with hyperkalemia as a presenting manifestation of Addison's disease can be very misleading. It is especially important to be vigilant of adrenal insufficiency in such patients as the hyperkalemia is resistant to standard therapy of insulin dextrose and can precipitate fatal arrhythmia if treatment is delayed.